Buddy, can you spare a dime? Homelessness, panhandling, and the public - Lee, Barrett A.; Farrell, Chad R. (2003)
The authors use data from two national surveys to shed light on panhandling among homeless people and the public's responses to it. A comparison of homeless panhandlers and nonpanhandlers shows the former group to be more isolated, troubled, and disadvantaged than the latter. Although only a minority of all homeless say that they panhandle, a majority of domiciled individuals report being panhandled, and most give at least occasionally. Such encounters have mixed but limited effects on the public's attitudes and behaviors. Overall, results challenge the notion that panhandling constitutes an especially threatening feature of urban life. The wisdom of anti-panhandling ordinances is discussed in light of this conclusion. - Reproduced.
Keywords: Homeless